Adapting to daily mobility difficulties? Insights from a major African city, Dakar - (:unkn) unknown (My University, 2023)
This study examines the daily mobility practices of urban residents in major African cities focusing on the case study of Dakar, Senegal. With population growth, urban sprawl, inadequate public transportation options, and limited motorized means among households, everyday travel proves to be both costly and difficult for many sub-Saharan African city residents. This article investigates the difficulties encountered by individuals in achieving their daily mobility needs and explores the adaptations they implement to meet their essential needs. To accomplish this, it draws upon a collection of 38 semi-structured interviews conducted with Dakar residents in 2022 and 2023, focusing on their daily mobility, as well as secondary analyses of a household mobility survey from 2015. It demonstrates how difficulties associated with the urban context and limitations in public transportation reinforce and exacerbate individual challenges in terms of physical strain, time loss, and financial pressure on household budgets. Urban dwellers, in response to these systemic transportation difficulties, employ various strategies as adjusting their current journeys by changing modes, routes, or destinations based on their requirements; pre-planning their trips and seeking financial or practical support; or accepting and resigning to the difficulties by internalizing them. The case of Dakar highlights the pervasive economic constraints in daily mobility and urban lifestyles in sub-Saharan Africa.
Keywords: African Research